2018
DOI: 10.1177/1747954118757436
|View full text |Cite
|
Sign up to set email alerts
|

Youth athletes' sustained involvement in elite sport: An exploratory examination of elements affecting their athletic participation

Abstract: In this exploratory study, we first intended to identify the underlying structure of components affecting the sport participation of 1258 elite youth athletes from the USA through a principal component analysis of 23 items related to motives and barriers to participation and created for this study. A six-component solution was proposed, including college and professional aspirations and competence beliefs, coach and peer relationships, pressures from parents and coach, intrinsic and self-determined extrinsic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…Comparing athletes of different genders, women have tended to score higher on intrinsic motivation and lower on extrinsic regulation than men (Amorose & Horn, 2001;Chantal et al, 1996;Duda et al, 1995;Pelletier et al, 1995;Petherick & Weigand 2002). Further, some studies have found that men achieved higher external regulation and amotivation than women (Nuñez et al, 2006;Wendling et al, 2018). Concerning the athletes' sport skill level, self-determination theory suggests that elite level athletes are more self-determined than recreational athletes (Mallett & Hanrahan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing athletes of different genders, women have tended to score higher on intrinsic motivation and lower on extrinsic regulation than men (Amorose & Horn, 2001;Chantal et al, 1996;Duda et al, 1995;Pelletier et al, 1995;Petherick & Weigand 2002). Further, some studies have found that men achieved higher external regulation and amotivation than women (Nuñez et al, 2006;Wendling et al, 2018). Concerning the athletes' sport skill level, self-determination theory suggests that elite level athletes are more self-determined than recreational athletes (Mallett & Hanrahan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…TPB also highlights that subjective norms are an essential component of intention, and that social factors such as parents' and coaches' influences are important determinants of intention to continue sport (Gucciardi & Jackson, 2015). Various studies have found that the relationship between motivational factors and sport continuation in the youth sport context is influenced by the type of support and pressures from parents, coaches, and peers (e.g., Jõesaar, Hein, & Hagger, 2011;Wendling, Flaherty, Sagas, & Kaplanidou, 2018). Wendling et al (2018) noted that when young people view participation in sport as more autonomous, their chances of sustaining involvement in sport increase.…”
Section: Attitude Formation and Intentionmentioning
confidence: 99%
“…Various studies have found that the relationship between motivational factors and sport continuation in the youth sport context is influenced by the type of support and pressures from parents, coaches, and peers (e.g., Jõesaar, Hein, & Hagger, 2011;Wendling, Flaherty, Sagas, & Kaplanidou, 2018). Wendling et al (2018) noted that when young people view participation in sport as more autonomous, their chances of sustaining involvement in sport increase. This is in line with what Ryan and Deci (2000) advanced within Self-Determination Theory (SDT).…”
Section: Attitude Formation and Intentionmentioning
confidence: 99%
“…While attrition rates have historically been highest in the adolescent years, macro-level research indicates that attrition rates among adolescents have been exacerbated by elevated competitive intensity, exclusivity, and early immersion in youth sport environments (Witt and Dangi, 2018 ; Aspen Institute, 2019 ). In contrast, motivation research, generally positioned in a post-positivist research paradigm, has generated a body of knowledge around how a youth sport climate in which the objectives of winning and early success supersede objectives around age-appropriate psychological, psychosocial, and physical development detract from youths' motivation to sustain participation (Petitpas et al, 2005 ; Wendling et al, 2018 ; Bateman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of research on supporting youth sport participation has centered on youths' motivation to participate in sport and the perceived benefits of participation. Among the primary motives to participate that youth identify are: (a) to have fun, (b) to be with friends, (c) to get exercise, and (d) for the excitement or challenge of competition (Fraser-Thomas et al, 2005 ; Balish et al, 2014 ; Wendling et al, 2018 ). Youth's motives for sport participation were derived from analyses primarily grounded in theory that is situated in a post-positive paradigm, such as Ryan and Deci's (2000) Self Determination Theory (SDT) of motivation and personality, in which micro-level processes are quantifiable determinants of motivation (Balaguer et al, 2017 ; Gould, 2019 ).…”
Section: Introductionmentioning
confidence: 99%